Benefit of implantable cardioverter defibrillator use in Japanese patients based on modified MADIT‐ICD benefit score - Toshinori Chiba; Yusuke Kondo; Yuki Shiko; Masahiro Nakano; Kajiyama Takatsugu; Miyo Nakano; Ryo Ito; Masafumi Sugawara; Yutaka Yoshino; Satoko Ryuzaki; Yukiko Takanashi; Yuya Komai; et al. (ESC Heart Failure)
Abstract Aims The MADIT‐ICD benefit score is used to stratify the risk of life‐threatening arrhythmia and non‐arrhythmic mortality. We sought to develop an implantable cardioverter defibrillator (ICD) benefit‐prediction score for Japanese patients with ICDs. Methods Patients who underwent ICD implantation as primary prophylaxis were retrospectively enrolled. Based on their MADIT‐ICD benefit scores, we developed a modified MADIT‐ICD benefit score adapted to the Japanese population. The primary endpoints were appropriate ICD therapy and all‐cause death without appropriate ICD therapy (non‐arrhythmic death). We used the Fine and Gray multivariate model and Cox proportional hazard regression to identify factors for adjusting the MADIT‐ICD benefit–risk score specifically for the Japanese population. The scoring points for the original MADIT‐ICD benefit score were adjusted to optimal points based on the multivariate analysis results in the population. Results The study enrolled 167 patients [age, 61.9 ± 12.3 years; male individuals, 138 (82.6%); cardiac resynchronization therapy, 73 (43.7%); ischaemic cardiomyopathy, 53 (31.7%)]. Fourteen patients received anti‐tachycardia pacing (ATP) therapy, and 23 received shock therapy as the initial appropriate ICD therapy. Non‐arrhythmic deaths occurred in 37 patients. The original MADIT‐ICD benefit score could not stratify non‐arrhythmic mortality in the Japanese population. The patients were reclassified into three groups according to the modified MADIT‐ICD benefit score. The modified MADIT‐ICD benefit score could effectively stratify the incidence of appropriate ICD therapy and non‐arrhythmic mortality. In the highest‐benefit group, the 10 year cumulative rates of appropriate ICD therapy and non‐arrhythmic mortality were 56.8% and 12.9%, respectively (P < 0.01). In the intermediate‐benefit group, these rates were 20.2% and 40.2% (P = 0.01). In the lowest‐benefit group, the incidence of non‐arrhythmic deaths was 68.1%, and no patient received appropriate ICD therapy. Conclusions The modified MADIT‐ICD benefit score may be useful for stratifying ICD candidates in the Japanese population.